Measurement of maize grain yield and aboveground biomass at maturity by crop cut at plot level - Murrell, T. Scott; Chivenge, Pauline P. (2023)
All measuring equipment requires calibration. Proper calibration requires additional equipment not listed here. We recommend consulting guidance published by The United States Bureau of Reclamation (USBR, 1989a,b,c): USBR-1000-89, USBR-1012-89, USBR-1020-89; the National Institute of Standards and Technology Office of Weights and Measures (NIST OWM, 2019a,b,c,d,e) standard operating procedures Nos 4, 5, 7, 8, 28; NIST Special Publication 250-31 (Davis, 1989); NIST Handbook 44 (Butcher et al., 2022); and NIST Handbook 159 (Lee and Olson, 2017). Record information about each measuring instrument: manufacturer, model number, date of last calibration certification, precision, weight limits, etc. At each experimental site, set up a processing area in the field. This area should be equipped with calibrated measuring equipment. Reserve at least one bag of each type as well as a few lengths of twine and any labels to tare the scales.